2010
DOI: 10.1038/nature09016
|View full text |Cite
|
Sign up to set email alerts
|

The Ectocarpus genome and the independent evolution of multicellularity in brown algae

Abstract: Brown algae (Phaeophyceae) are complex photosynthetic organisms with a very different evolutionary history to green plants, to which they are only distantly related(1). These seaweeds are the dominant species in rocky coastal ecosystems and they exhibit many interesting adaptations to these, often harsh, environments. Brown algae are also one of only a small number of eukaryotic lineages that have evolved complex multicellularity (Fig. 1). We report the 214 million base pair (Mbp) genome sequence of the filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
856
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 813 publications
(885 citation statements)
references
References 29 publications
21
856
2
6
Order By: Relevance
“…Of the known classes of repetitive elements, LTR retrotransposons were the most abundant group of annotated repeats (6%) (Fig. S3a–c), similar to previous reports in other diatoms (Maumus et al ., 2009), as well as other Stramenopiles (Cock et al ., 2010; Ye et al ., 2015), yeast (Bleykasten‐Grosshans & Neuvéglise, 2011) and some flowering plants (Bennetzen, 2005). To investigate the role of LTRs in shaping the genomic structure of P. multistriata , a de novo search specific for complete LTR elements was performed in the genomes of five diatoms and that of Oryza sativa .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the known classes of repetitive elements, LTR retrotransposons were the most abundant group of annotated repeats (6%) (Fig. S3a–c), similar to previous reports in other diatoms (Maumus et al ., 2009), as well as other Stramenopiles (Cock et al ., 2010; Ye et al ., 2015), yeast (Bleykasten‐Grosshans & Neuvéglise, 2011) and some flowering plants (Bennetzen, 2005). To investigate the role of LTRs in shaping the genomic structure of P. multistriata , a de novo search specific for complete LTR elements was performed in the genomes of five diatoms and that of Oryza sativa .…”
Section: Resultsmentioning
confidence: 99%
“…The genome size, N50 value and GC content were taken from the respective publications (Armbrust et al ., 2004; Bowler et al ., 2008; Cock et al ., 2010; Lévesque et al ., 2010; Lommer et al ., 2012; Tanaka et al ., 2015; Mock et al ., 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Flavonoids are another group of compounds thought to protect against ultraviolet radiation in terrestrial plants [37]. A pathway of flavonoid biosynthesis including many homologues genes related to the terrestrial plant was identified in P. yezoensis, and this pathway was also found in Ectocarpus but was completely absent from diatom or green algal genomes [38]. It was worth noting that LI818 family proteins, the light-stress related LHCs, were failed to be identified in the pool of unigenes.…”
Section: Stress-tolerance Mechanismsmentioning
confidence: 99%
“…Some GL responses, although less effective than BL or RL, have already been reported to have a role in morphogenesis in the brown alga, Scytosiphon lomentaria (Dring and Lüning 1975) and in chloroplast movement in the centric diatom, Pleurosira laevis (Furukawa et al 1998). Recently, genome analysis of 2 diatom species, Thalassiosira pseudonana and Phaeodactylum tricornatum, and 1 brown alga, Ectocarpus siliculosis, revealed that they conserve many BL receptors, such as cryptochromes, LOV-histidine kinases and aureochromes, or the chromophore binding domain of phytochrome, GAF domain (Armbrust et al 2004, Bowler et al 2008, Cock et al 2010. However, the well-known GL receptor rhodopsin was missing from these genomes.…”
Section: Correlation Between Morphology and Motilitymentioning
confidence: 99%